The Importance of the Research in Construction History for the Safeguard and Valorization of the Architectural Heritage. The Example of the Bourgeois Houses of the City of Porto - Rui Póvoas (2014)
In recent times, the most developed countries have been responsible for the production of a surplus increasingly untenable, with serious consequences for the natural resources and for the environment. In the case of housing, this problem is aggravated, such is the dimension of its impact. In a near future, the new paradigm centred in the intervention on the existing buildings, will impose, necessarily, a change in the design process. In this context, the research in Construction History reveals itself of the most importance, given its contribution for the knowledge of the techniques and the constructive systems of the past. This fact, actually, it is so much more relevant the greater is the patrimonial value of the object of study. It is proposed to present the methodology that has guided the characterization and typification of the constructive system of the bourgeois houses of Porto, work that, initially, has aimed to give a contribution to the Construction History in Portugal, and that, subsequently, has served for the conception of a methodology of intervention in this important example of architectural heritage. Starting from the surveys accomplished in the scope of academic works, the research on the constructive system of these buildings has been complemented and validated with the dispersed information taken from available old manuals and from scientific studies conducted on the subject, assuming, in this study, drawing as the main tool of interpretation and systematization of the accomplished work.